Successful venture building: What matters! An empirical examination of effective incubation practices - THNG, Patrick (Institutional Knowledge at Singapore Management University, 2019)
Incubator models have evolved since the first known US incubator in 1959. From the first generation of a facilities-focused incubator model in the 1960s to the fourth generation of emerging models, commonly referred to as, the “Accelerator” model and the “Venture Builder” model. Since 2006, there has been a significant increase in the number of venture builders and accelerators. Yet very little is known about a) their performance and the antecedents; b) the key differences between venture builders and accelerators; c) the factors and practices that characterise highly successful venture builders and d) their (venture builders)comparative advantages or disadvantages compared to the large number of accelerators. This study examined and analysed the venture building phenomenon where there has been a paucity of rigorous published scientific research. Meanwhile, practice-oriented publications have proliferated. The empirical research adopted both face-to-face interviews and online semi-structured surveys that comprised three separate studies. Study 1 saw the participation of eight overseas and local incubation practitioners in separate face to face hour-long interviews (four accelerators and four venture builders). The literature review and the findings in Study 1, which detailed the actual practices of these two incubation models, yielded ten key important practices that these incubators represented as their modus operandi. These ten practices became the independent predictors which were used in Study 1a and Study 2. Study1a was an extension of Study 1 in that twenty-nine highly experienced incubation practitioners (from diverse location such as Hungary, US, Canada, Portugal, France, Mexico and Turkey) participated in answering an online semi-structured survey to ascertain their agreement or disagreement about these ten practices as characteristics of venture building practices. Finally, Study 2, an online semi-structured survey, was launched. Study 2 yielded responses from forty-four start-ups from wide-ranging diverse countries including Singapore, Canada, US, Thailand, Turkey, India and Japan. This was the focal study that provided the data for testing eleven pairs of hypotheses. Success, being the predicted outcome of the start-ups was assessed from two angles - financial success and psychological satisfaction. The study identified the key incubation practices that were associated with successful start-ups and produced a binomial logistic regression generated prediction model for each of the two success outcomes. Together the findings of the three studies were triangulated and yielded eight key insights on the predictors that contributed to successful start-ups. To develop financially successful start-ups, incubators should focus on the five key practices of marketing performance, demand orientation, market scope, internationalisation and long-term engagement; whereas in developing psychologically satisfied start-ups, the four key focal practices are marketing performance, demand orientation, market scope and internationalisation (high commonality with practices identified for financially successful start-ups). This exploratory research contributed to our innovation knowledge by exploring the known gaps and provided key insights that are useful for start-up investors, government innovation policy-makers and entrepreneurs of start-ups looking to maximise success. The study concluded by suggesting some areas for future research. The key takeaway of this research is this: “Given the often-confusing labelling of incubators as accelerators or venture builders, it is not what they call themselves that is critical to the success of start-ups - but what they actually practice that matters !”.